Energetic parameters of rowing performance: Will the distance change in the 2028 Los Angeles Olympic Games matter? - Boillet, A.; Messonnier, L. A.; Cohen, C. (Medicine & Science in Sports & Exercise, 2025)
Purpose The study aimed to model rowing in a single scull, considering individual physiological characteristics of rowers, to determine the optimal pacing strategy over 2000 m (current Olympic distance) and 1500 m (future Olympic distance for 2028), as well as the sensitivity of performance to specific physiological factors at these distances.